2018
DOI: 10.1038/s41598-018-22085-3
|View full text |Cite
|
Sign up to set email alerts
|

Nanobody-Displaying Flagellar Nanotubes

Abstract: In this work we addressed the problem how to fabricate self-assembling tubular nanostructures displaying target recognition functionalities. Bacterial flagellar filaments, composed of thousands of flagellin subunits, were used as scaffolds to display single-domain antibodies (nanobodies) on their surface. As a representative example, an anti-GFP nanobody was successfully inserted into the middle part of flagellin replacing the hypervariable surface-exposed D3 domain. A novel procedure was developed to select a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…ing Information, Figure S3 A). This is at least an approximately 10 000-fold impairment compared to the binding constant reported for the wild-type nanobody (1; K d = 1.1 nm for sfGFP [17] and 0.6 nm for GFP [13] ). Unexpectedly,the NPYcaged photobody (5)w as less impaired (approximately 420fold), with a K d of 0.46 AE 0.02 mm (Supporting Information, Figure S3 B).…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…ing Information, Figure S3 A). This is at least an approximately 10 000-fold impairment compared to the binding constant reported for the wild-type nanobody (1; K d = 1.1 nm for sfGFP [17] and 0.6 nm for GFP [13] ). Unexpectedly,the NPYcaged photobody (5)w as less impaired (approximately 420fold), with a K d of 0.46 AE 0.02 mm (Supporting Information, Figure S3 B).…”
mentioning
confidence: 60%
“…[19] Prior to irradiation of the presenting cells,nosfGFP binding could be detected for concentrations up to about 10 mm,consistent with the results from our MST assay.Wethen added sfGFP to cells that had been irradiated for 45 s( l = 365 nm) and could determine a K d of 0.90 AE 0.03 nm ( Figure 3E), nicely fitting with the positive control and consistent with the previously reported binding constant of the wild-type anti-GFPenhancer nanobody. [13,17] Together, these results demonstrated that the photodeprotected photobody regains its full antigen binding affinity.…”
mentioning
confidence: 68%
“…We have also developed a high-affinity version of the split CL intein by fusing a nanobody-epitope pair to the N-and C-terminal intein fragments. Importantly, this proximity-conferring dimerization system can be encoded fully recombinantly (68), in contrast to previous semisynthetic interaction pairs (57,69), and exploits the low nanomolar affinity of the anti-GFP nanobody/eGFP complex (49,50). Specific fluorescent labeling of membrane receptors on the surface of mammalian cells was possible with the labeled CysTagintein part added to the growth medium in concentrations as low as 10 nM.…”
Section: Discussionmentioning
confidence: 99%
“…4C). The efficient binding of the labeled nanobody at such a low concentration close to its K d value (around 1 nM) (49,50) indicated that its binding capacity was completely preserved.…”
Section: Selective N-terminal Chemical Modification Of Proteins Undermentioning
confidence: 97%
“…The bacterial flagellum is a locomotive organelle that includes a membrane-embedded nanomotor that rotates long helical filaments. Flagellar filaments are natural protein nanotubes with an outer diameter of 23 nm, which can raise to 20 μm [84]. This indicated that flagellum has extraordinary mechanical properties as it is extremely rigid and has an elastic modulus estimated at The bacterial flagellum is a locomotive organelle that includes a membrane-embedded nanomotor that rotates long helical filaments.…”
Section: Characteristics Of Bacterial Flagella In Comparison With Carmentioning
confidence: 99%